Offensive Weapons of the Akkoyunlu Army - Nariman Shiraliyev (Universal Journal of History and Culture)
The study aims to clarify the offensive weapons used by the military units of the Akkoyunlu state on the battlefield, to determine the technical characteristics of these weapons, and to reveal the areas of their use by the warriors. The research was carried out based on first-hand sources of the period, and the scientific basis of other scientific studies based on these sources was also used. As a result of the research, the assault weapons used by the Akkoyunlu army were analysed under two sub-headings: short-range assault weapons and long-range assault weapons, taking into account their range of use and techniques, and a total of nine military weapons were discussed. In addition to the more actively used weapons of the period, such as the bow and arrow, spear, sword, axe, mace, catapult, and ballista, less commonly used weapons, such as firearms, tatar bow, and javelin, were also included in the study. The technical specifications of these weapons are also included, along with their use and application areas on the battlefield.